Impact of Land Subsidence-Induced Three-Dimensional Surface Deformation on Infrastructure in the Semarang-Demak Alluvial Plain, Indonesia - Azeriansyah, Reyhan; Ching, Kuo-En; Darmo Yuwono, Bambang (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2025)
We estimated surface deformation using SBAS-InSAR and the Mogi Source Model is then adopted to elucidate the mechanisms and spatial variability of surface deformation within the Semarang-Demak Alluvial Plain and its impacts on infrastructures. By analyzing predicted vertical and horizontal velocities, we identify intensive groundwater extraction as the primary driver of aquifer compaction, with vertical subsidence exceeding -120 mm/year and volume loss rates surpassing -6,000 m³/year in the urbanized Semarang-Demak region. These findings highlight the three-dimensional characteristics of deformation, forming a characteristic “bowl-shaped” pattern and revealing the sensitivity of infrastructure—expressways, railways, national roads, local roads, and airports—to high strain and tilt gradients. The integrated analysis thus underscores the necessity of sustainable groundwater management and adaptive land-use strategies to mitigate deformation-induced risks. This approach is crucial for safeguarding the long-term functionality and resilience of vital infrastructure in this subsidence-prone coastal region, guiding decision-makers toward strategic and sustainable development practices.